Multi-resources Risk Factors Predicting the Neurodevelopmental Disorders Among Children in Occupied Palestine - Mr. Khader Mahmoud Rasras (Journal of College of Education, 2024)
The study objective was to identify the intricate interplay of various factors – encompassing familial, environmental, health-related, conception-period-related, and delivery-condition-related elements – that may serve as confounding risk factors in predicting the occurrence of Neurodevelopmental Disorders (NDDs). The study community was composed of mothers of children with NDDs in the northern governorates of occupied Palestine, whose children attend care centers. The study employed a purposive and accessible sampling method composed of 175 mothers of children with NDDs, and mothers of Typically Developing children (n=30). The study is a descriptive analytic approach. The Study tool was a specially tailored multifaceted questionnaire. The results showed significant relationship between a child's birth weight and health status, parental kinship, and the presence of other disabled relatives. The exposure of either mothers or children to tear gas and health complications also displayed significant connections. Furthermore, maternal exposure to severe stress, violence, prophylactic drug usage, or exposure to X-rays emerged as impactful factors. Delivery circumstances were identified as significant elements, alongside the child's health conditions and exposure to Tear Gaz. The study recommends the creation of a developmental milestones portfolio to track progression.
Keywords: Neurodevelopmental Disorders, Neurological Soft Signs and Risk Factors